Strings of Unity isang pag-aaral ng International Rondalla Festival (Cuerdas) bilang pamamahala sa sining sa Pilipinas - Vitto, Loen (2022)
“Strings of Unity: Isang Pag-aaral ng International Rondalla Festival (Cuerdas) Bilang Pamamahala sa Sining sa Pilipinas” is a preliminary study on the concepts and ideas of arts management in the Philippines as a discipline. These ideas and concepts shall be presented through the process of management of the Strings of Unity: The International Rondalla Festival, or commonly known as Cuerdas — a music festival featuring plucked string instruments which includes the Philippine rondalla and other plucked string instruments from around the world.

Presented here is the concept of management as written by Derrick Chong, which features the concepts of arts management as Classical Industrial Economy or a practice concerning production, distribution, and consumption; the responsibilities of the arts organization — artistic integrity, access, public accountability, and managing stakeholders. These arts managements concepts will be placed and compared to the process of management of Cuerdas. Cuerdas included additional components encompassing these management concepts (production and consumption), such as the cultural education, research, and training programs. This paper will present an expanded management model as implemented in Cuerdas festival.
Keywords: Strings of Unity; Arts Management; Music festivals